2019
DOI: 10.7150/ijbs.33837
|View full text |Cite
|
Sign up to set email alerts
|

Treatment implications of natural compounds targeting lipid metabolism in nonalcoholic fatty liver disease, obesity and cancer

Abstract: Metabolic disorders can lead to a scarcity or excess of certain metabolites such as glucose, lipids, proteins, purines, and metal ions, which provide the biochemical foundation and directly contribute to the etiology of metabolic diseases. Nonalcoholic fatty liver disease, obesity, and cancer are common metabolic disorders closely associated with abnormal lipid metabolism. In this review, we first describe the regulatory machinery of lipid metabolism and its deregulation in metabolic diseases. Next, we enumera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 84 publications
(78 reference statements)
0
27
0
1
Order By: Relevance
“…Furthermore, there are molecules that induce apoptosis in different types of cancer by acting specifically on SCD1 [14]. The inhibition of SCD1 through natural compounds can result in health benefits [16][17][18]. The sterculic oil is an extremely precious natural product, capable of inhibiting SCD1 enzyme in obese ob/ob mice, reducing fat accumulation in the liver and adipose tissue and improving inflammation and insulin resistance, factors that create an environment conducive to the development of cancer [17].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there are molecules that induce apoptosis in different types of cancer by acting specifically on SCD1 [14]. The inhibition of SCD1 through natural compounds can result in health benefits [16][17][18]. The sterculic oil is an extremely precious natural product, capable of inhibiting SCD1 enzyme in obese ob/ob mice, reducing fat accumulation in the liver and adipose tissue and improving inflammation and insulin resistance, factors that create an environment conducive to the development of cancer [17].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, MeJA application in our research not only stimulated the presence of (E)‐β‐farnesene but also increased its content. As natural compounds that widely exist in plants, terpenoids could be divided into monoterpenes, sesquiterpenes, diterpenes, sesterterpenes, triterpenes, tetraterpenes and polyterpenes, among which monoterpenes and sesquiterpenes are common 44 . Classification revealed that terpenoids were dominant in S japonicus flowers, such as α‐pinene, ocimene, myrcene and germacrene‐d.…”
Section: Discussionmentioning
confidence: 99%
“…ACC is phosphorylated by two upstream factors: AMPK and PPAR-α (Lee & Kim, 2010;Smith et al, 2016;Cheng et al, 2019). We measured the changes in AMPK and PPAR-α expression to identify which factor is related to ACC inhibition following TGPN administration.…”
Section: Regulation Of Lipid Metabolism-related Proteins By Tgpn Administrationmentioning
confidence: 99%